KONSEP PROFIL GURU DAN SISWA (MENGENAL PEMIKIRAN AL-ZARNUJI DALAM TA'LIM AL MUTA'ALLIM DAN RELEVANSINYA) - Miftahuddin, Miftahuddin (Jurnal Cakrawala Pendidikan, 2016)
This article attempts toreveal the necessitu of Al-Zarnuji's views in Ta'li, Al-Muta'allim to be actualized into a meyodology of education. The revelation is based on the observation that some concepts in Ta'lim Al-Muta'aliim appear to remain tmelessly relevant to be adopted as educational principles by educators and students a like in the achievements of educational goals.